Motivation of male adolescents to become perpetrators of violence: a study of phenomenology - Munqidz Zahrawaani; Nani Nurhaeni; Allenidekania Allenidekania (SAGE Publishing, 2021)
Background: Violence committed by adolescents is a serious public health problem. More than ten percent of youth violence have been subjected to violence and more than fifty percent attacks and serious violence. Design and Methods: A qualitative study with a phenomenological study design in which semi-structured interviews were conducted with participants who were once challenged by violence and are now kept in LPKA Class II Jakarta. Results: This qualitative study explores adolescent motivation to become violent perpetrators. This study discusses four major themes, namely, i) Unsafe environmental conditions; ii) Unpleasant past experiences; iii) Childhood trauma; and iv) Peer group solidarity or friendship. Conclusions: Adolescent motivational advice provides protection for students in Indonesia to participate in discussions about children related to challenges or assistance that can be given to adolescents so as not to offend again.